Mucin-1 Gene Mutation and the Kidney: The Link between Autosomal Dominant Tubulointerstitial Kidney Disease and Focal and Segmental Glomerulosclerosis - H. Trimarchi; M. Paulero; T. Rengel; I. González-Hoyos; M. Forrester; F. Lombi; V. Pomeranz; R. Iriarte; A. Iotti (Case Reports in Nephrology)
Glomerular diseases are one of the most frequent causes of chronic kidney disease, focal and segmental glomerulosclerosis being one of the commonest glomerulopathies. However, the etiology of this glomerular entity, which merely depicts a morphologic pattern of disease, is often not established and, in most of the patients, remains unknown. Nephrologists tend to assume focal and segmental glomerulosclerosis as a definitive diagnosis. However, despite the increasing knowledge developed in the field, genetic causes of glomerular diseases are currently identified in fewer than 10% of chronic kidney disease subjects. Moreover, unexplained familial clustering among dialysis patients suggests that genetic causes may be underrecognized. Secondary focal and segmental glomerulosclerosis due to genetic mutations mainly located in the podocyte and slit diaphragm can occur from childbirth to adulthood with different clinical presentations, ranging from mild proteinuria and normal renal function to nephrotic syndrome and renal failure. However, this histopathological pattern can also be due to primary defects outside the glomerulus. The present report illustrates an adult case of secondary focal and segmental glomerulosclerosis with a dominant tubulointerstitial damage that led to the pursue of its cause at the tubular level. In this patient with an undiagnosed family history of adult kidney disease, a genetic study unraveled a mutation in the mucin-1 gene and a final diagnosis of adult dominant tubular kidney disease-MUC1 was made.